Tamtsil Al Marah Fi Majmuati Qashaid “Anta-Lii” Li Nizar Qabaani Bi Nadzariyah Michael Riffatere - Soni Fauzi; Dzun Nur Nafi’ah Muamaroh; Arief Rahman Hakim; Khafid Roziki (Journal of Arabic Literature (JaLi), 2022)
This research aims to know the indicative reading, the hermeneutic reading, and the indirect expression of the representation of women in the collection of poems "You are mine" by Nizar Qabbani by Michael Rifter. The research questions are. 1) What is the indicative reading (Heuristik) and hermeneutic reading (Hermeneutik) in Nizar Qabbani’s collection of poems ”Anti Lii” according to Nizar Qabbani? 2) What is the indirect expression of the representation of women in the collection of Nizar Qabbani's poems "Anti Lii" by Michael Riffatere? Semiotics is the science of signs in a context in which people's lives are discussed directly and pictorially. Semiotics can also be the study of signs found about human life. Poetry is in fact mainly created by the author according to his life experience and social environment. The type of research in this research is desk study. The research method used in this research is qualitative and descriptive. And the way to put data in a way to read and write. To analyze the data, the method used is Mills and Huberman, which consists of three stages, namely: the method of data collection, data reduction, and drawing conclusions. The result of this research is in a collection of poems you are mine entitled, clothes, blue swimsuits and he in each stanza contains elements of heuristic and heurmenetic meanings. Among the indirectness of expression in the poem entitled clothes there are 5 words, the pink nightgown poem is in 5 words and in the poem entitled swimsuit there are 7 words which indicate the indirectness of expression and describe representasion about woman